Predictors of Employment Outcomes for People with Visual Impairment in Taiwan: The Contribution of Disability Employment Services. (November 2013) - Jang, Yuh; Wang, Yun-Tung; Lin, Meng-Hsiu; Shih, Kevin J.
Introduction: We investigated the employment status and identified factors that may affect the employment outcomes of people with visual impairments in Taiwan. Methods: A retrospective, ex post facto design study was conducted. The sample included 313 visually impaired clients who commenced and "closed" (completed) disability employment services between 2008 and 2010 in a metropolitan area in Taiwan. Results: Two hundred and seventy-one out of 313 (87%) clients were gainfully employed after receiving services. Among those employed, 224 clients were employed as massage practitioners. Factors that increased the likelihood of successful employment outcomes after receiving services included more postemployment services, fewer pre-employment services, and having a vocational qualification. Discussion: This study provides some empirical support documenting the association between the provision of employment services and employment outcomes among people with visual impairments in Taiwan. Implications for practitioners: The importance of disability employment services programs, a major component of vocational rehabilitation services, within the overall operation of rehabilitation is their capacity to provide direction, focus, and meaning to other therapies or services. The results of this study may lead employment specialists to reexamine their case services practices. Knowledge of factors that may affect clients' rehabilitation may help employment specialists to better estimate how much support and training are needed and better assess their clients' employability.